2021
DOI: 10.1007/s00227-021-03824-z
|View full text |Cite
|
Sign up to set email alerts
|

Southwestern Atlantic reef-building corals Mussismilia spp. are able to spawn while fully bleached

Abstract: Bleaching events are becoming more frequent and intense worldwide. Southwestern Atlantic corals are considered stresstolerant species that suffer less during bleaching episodes. Therefore, we investigated if the reef-building corals Mussismilia hispida and M. harttii are capable of spawning while fully bleached. We compared spermatozoa concentration and motility, egg diameter and embryo viability between seemingly healthy and bleached colonies for both species. Findings show that both species spawned viable ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Because oocyte size is correlated with maternally provisioned lipids, this response is hypothesized to ensure adequate energy is available for all of the now limited number of oocytes to survive through settlement 25 . Since we observe a similar phenomenon to this study, it is possible that the strategy of producing fewer high quality oocytes over more low quality oocytes is specific to Acropora, as opposed to other coral genera where this strategy has not been observed 21 , 23 , 30 . In A. hyacinthus, bleaching stress appears to induce energetic constraints on reproduction, resulting in hosts provisioning a baseline level of nutrients into oocytes, with the number of oocytes being limited by the energetic costs of recovery.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Because oocyte size is correlated with maternally provisioned lipids, this response is hypothesized to ensure adequate energy is available for all of the now limited number of oocytes to survive through settlement 25 . Since we observe a similar phenomenon to this study, it is possible that the strategy of producing fewer high quality oocytes over more low quality oocytes is specific to Acropora, as opposed to other coral genera where this strategy has not been observed 21 , 23 , 30 . In A. hyacinthus, bleaching stress appears to induce energetic constraints on reproduction, resulting in hosts provisioning a baseline level of nutrients into oocytes, with the number of oocytes being limited by the energetic costs of recovery.…”
Section: Discussionsupporting
confidence: 82%
“…Oocyte size is an indicator of maternal condition; individuals with larger energy reserves are able to provision more proteins and lipids to their oocytes and thus produce larger oocyte sizes 43 , 49 . A decrease in oocyte size is often observed as a consequence of severe stresses such as coral bleaching 21 , 23 , 30 , yet we found remarkably similar distributions and averages of oocyte sizes between resistant and recovered colonies, despite clear differences in gamete presence. A study of Acropora millepora demonstrated that under thermal stress, colonies maintained oocyte sizes across bleaching phenotypes, but produced fewer oocytes compared to when they reproduced under non-bleached conditions 25 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, in adult polyps the nutritional balance shifts towards the primacy of the symbiosis 19,20 , including our observation of a striking reliance on symbiosis for Aiptasia sexual reproduction. This has been observed in the Hydra/Chlorella symbiosis 21 , and although some aposymbiontic corals can spawn 22 , the breakdown of symbiosis likewise rather severely affects sexual reproductive success in corals (e.g. 23 )…”
Section: Role Of Symbiosismentioning
confidence: 95%